2017
DOI: 10.1002/jcla.22125
|View full text |Cite
|
Sign up to set email alerts
|

Maternal IGF1 and IGF1R polymorphisms and the risk of spontaneous preterm birth

Abstract: Our findings suggest that polymorphisms of IGF1 rs972936 and IGF1R rs2229765 were associated with the risk of SPTB in Chinese pregnant women and these effects depend on the maternal metabolic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…[27] Among Chinese pregnant women, those carrying GA/AA genotypes were more likely to have spontaneous preterm infants. [28] However, the effects of these three polymorphisms on individual susceptibility to ONFH had been rarely reported in Chinese Han population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27] Among Chinese pregnant women, those carrying GA/AA genotypes were more likely to have spontaneous preterm infants. [28] However, the effects of these three polymorphisms on individual susceptibility to ONFH had been rarely reported in Chinese Han population.…”
Section: Discussionmentioning
confidence: 99%
“…These results were in line with the relevant studies carried out in other types of human disease. [2628] In addition, strong linkage disequilibrium was observed between polymorphisms rs5742714 and rs972936. Haplotype analysis demonstrated that the haplotype C-T dramatically elevated the susceptibility to ONFH when compared to C-C, while G-T decreased the individual susceptibility to ONFH among Chinese Han population.…”
Section: Discussionmentioning
confidence: 99%
“…Although the investigators concluded that ligands of IGF1R that regulate IGF1R dependent signaling cascades are associated with sPTB 16 , how dysregulation of IGF1R signaling itself can be involved in sPTB was not addressed. A candidate gene-based association study on the Chinese population identified an SNP in IGF1R (rs2229765) which is associated with reduced risk of sPTB in women with GA or AA genotype as compared to the women with GG genotype 17 . A study in mouse and human breast tumor epithelial cell lines reported that downregulation of IGF1R expression increases cellular stress and cytokine (IL-6 and CCL2) production 18 .…”
Section: Genomic Approaches To Study Sptbmentioning
confidence: 99%
“…According to statistics, perinatal mortality is as high as 70% in low birth weight (LBW) with neonatal weight below 2,500 g ( Hack et al, 1994 ; Rutter, 1995 ), most of them are born preterm. Growing evidence has shown that the incidence and development of PTB is a complex process that is influenced by a variety of environmental and genetic factors ( He et al, 2017 ; Liu et al, 2017 ; Qiu et al, 2017 ; Xiao et al, 2016 ). Therefore, it is helpful to develop approaches of effective prevention and treatment of neonatal morbidity and mortality by elucidating etiological factors contributing to PTB or LBW.…”
Section: Introductionmentioning
confidence: 99%